A Coupled Mathematical Model for the Synthesis of Composites - Knyazeva, Anna G.; Bukrina, Natalia V. (Journal of Siberian Federal University. Mathematics & Physics, 2020)
The work proposes a model for synthesizing a composite "metallic matrix–reinforcing inclusions". The solution is based on two algorithms demonstrating similar results. It is shown that, like in classic models of combustion, there is a domain of model parameters where a transition to the stationary regime is possible. It is demonstrated that taking into account the thermal and mechanical processes alters the effective properties (thermal capacity and thermal effects of the reaction) and provokes the formation of a new heat source conditioned by the interaction of different physical processes